1976
DOI: 10.1107/s0567740876010194
|View full text |Cite
|
Sign up to set email alerts
|

N-Carboxy-L-alanine anhydride

Abstract: C4NO3Hs, M= 115.09; orthorhombic, P212t21; a=7.749 (2), b=10.699 (3), c=6.063 (2) A; Z=4, Dm= 1"52 (by flotation), Dx= 1.52 g cm -3. The compound was synthesized from L-alanine and trichloromethyl chloroformate, and crystallized from isopropyl ether at -5°C. The final R value was 0.047 for 681 reflexions. The molecules are linked by weak hydrogen bonds formed between N(1)-H(1) and 0(3') in the b direction.Introduction. The N-carboxy anhydrides (NCA) of amino acids are the most useful monomers for the synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The crystal structures of L-amino acid NCAs have been determined by the author et al [10][11][12][13][14][15][16]. The crystal data are given in Table 25.4.…”
Section: Crystal Structurementioning
confidence: 99%
“…The crystal structures of L-amino acid NCAs have been determined by the author et al [10][11][12][13][14][15][16]. The crystal data are given in Table 25.4.…”
Section: Crystal Structurementioning
confidence: 99%
“…The crystal structures of amino acid NCAs were not studied for many years after the very early initial report by Leuchs (1906). We have reported the crystal structures of glycine NCA (Kanazawa et al, 1976a) and l-alanine NCA (Kanazawa et al, 1976b), and found that the ease of polymerization depended on the crystal structure (Kanazawa & Kawai, 1980). In addition, the crystal structures of -benzyl-l-glutamate NCA (Kanazawa et al, 1978a), l-leucine NCA (Kanazawa et al, 1978b), l-valine NCA (Kanazawa et al, 1984), dl-valine NCA (Takenaka et al, 1994), dl-phenylalanine NCA (Kanazawa et al, 1997), l-phenylalanine NCA and -benzyl-l-aspartate NCA (Kanazawa & Magoshi, 2003) have also been determined.…”
Section: Commentmentioning
confidence: 99%
“…The present author determined the crystal structures of glycine NCA (Kanazawa et al, 1976a) and l-alanine NCA (Kanazawa et al, 1976b) and discussed their polymerizability with reference to the crystal structure (Kanazawa & Kawai, 1980). In addition, the crystal structures of -benzyl-l-glutamate NCA (Kanazawa et al, 1978a), l-leucine NCA (Kanazawa et al, 1978b), l-valine NCA (Kanazawa & Ohashi, 1984), dl-valine NCA (Takenaka et al, 1994) and dl-phenylalanine NCA (Kanazawa et al, 1997) have been determined.…”
Section: Commentmentioning
confidence: 99%